Company Responsibility for Workers' National Health Insurance Rights Due to Termination of Employment - Wulandari, Anggi Yudistia; Gorda, A.A.A Ngurah Sri Rahayu; Kurniawan, I Gede Agus; Gorda, A.A.A Ngurah Tini Rusmini (Faculty of Law, Universitas Pekalongan, 2024)
Labor law requires companies to provide health insurance to their workers as part of workers' rights protected by law. The company's responsibility for health insurance for workers affected by layoffs is an important issue in terms of workforce protection. In practice, there are still many companies that do not fully understand and implement these obligations, resulting in uncertainty regarding health protection for workers. In the event of job termination, many workers lose access to health insurance, leaving them vulnerable to health risks without protection because health insurance often stops at the same time the employment relationship ends. This research aims to analyze the legal obligations for companies to register their workers as health insurance participants, and identify the legal consequences for companies that do not fulfill their obligations regarding workers' health insurance rights after termination of employment.